2004
DOI: 10.1002/art.20052
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL induces apoptosis of chondrocytes and influences the pathogenesis of experimentally induced rat osteoarthritis

Abstract: Objective. To investigate whether TRAIL influences the pathogenesis of osteoarthritis (OA).Methods. A recombinant adenoviral vector system (Ad- Conclusion. TRAIL induces chondrocyte apoptosis, and TRAIL-induced chondrocyte apoptosis may play a role in the pathogenesis of OA.TRAIL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
58
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 68 publications
3
58
0
1
Order By: Relevance
“…In addition, it seems to reduce inflammation and inhibit MMP expression by increasing AMP and inhibiting the p38/ JNK pathway (19). Previous studies have demonstrated that cilostazol inhibits apoptosis under several circumstances (12,(20)(21)(22). In those studies, cilostazol was shown to prevent lipoprotein particle-induced apoptosis in human umbilical vein endothelial cells (HUVECs) (22), lipopolysaccharide-induced apoptosis in HUVECs (20), and ischemic injury-induced apoptosis in neural cells (12,21).…”
Section: Conclusion Our Findings Indicate That Cilostazol Prevents Nmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it seems to reduce inflammation and inhibit MMP expression by increasing AMP and inhibiting the p38/ JNK pathway (19). Previous studies have demonstrated that cilostazol inhibits apoptosis under several circumstances (12,(20)(21)(22). In those studies, cilostazol was shown to prevent lipoprotein particle-induced apoptosis in human umbilical vein endothelial cells (HUVECs) (22), lipopolysaccharide-induced apoptosis in HUVECs (20), and ischemic injury-induced apoptosis in neural cells (12,21).…”
Section: Conclusion Our Findings Indicate That Cilostazol Prevents Nmentioning
confidence: 99%
“…In those studies, cilostazol was shown to prevent lipoprotein particle-induced apoptosis in human umbilical vein endothelial cells (HUVECs) (22), lipopolysaccharide-induced apoptosis in HUVECs (20), and ischemic injury-induced apoptosis in neural cells (12,21). Notably, protein kinase CK2 (PKCK2) was reported to be involved in the prevention of apoptosis by cilostazol (12,23).…”
Section: Conclusion Our Findings Indicate That Cilostazol Prevents Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased chondrocyte density and cell death are considered features of OA cartilage (8). Several potential mechanisms of chondrocyte death have been proposed, including production of oxygen and nitrogen radicals, death receptor activation, and mechanical stress (9)(10)(11). GAG loss is known to occur in response to mechanical injury and is linked with chondrocyte death (12,13).…”
mentioning
confidence: 99%